An evaluation of the Cactaceae of Barbados, Grenada, Saint Vincent, and The Grenadines - Hoxey, Paul; Gdaniec, Andrew (Phytotaxa, 2021)
Three species of Cactaceae are considered native to Barbados and eight species to Grenada and Saint Vincent and The Grenadines. Melocactus intortus is reported for the first time from The Grenadines and the identity of Selenicereus innesii, a Saint Vincent endemic, is clarified. Lectotypes for Melocactus broadwayi, Cereus margaritensis, and Cereus grenadensis are proposed. Cereus plumieri, which was described on the basis of a Plumier’s illustration published 300 years ago, is finally observed in habitat and a new combination made in the genus Selenicereus. Morphological descriptions and distributions of the recognized species are provided.